Software reliability modeling with testing-effort function and imperfect debugging - ZHAO Qian; ZHENG Jun; LI Jing (Institute of Advanced Engineering and Science, 2012)
Considering testing effort and imperfect debugging in reliability modeling process may further improve the fitting and prediction results of software reliability growth models (SRGMs). For describing the S-shaped varying trend of the testing-effort increasing rate more accurately, this paper first proposes a inflected S-shaped testing effort function (IS-TEF). Then this new TEF is incorporated into the inflected S-shaped NHPP SRGMs for obtaining a new NHPP SRGMs which consider S-shaped TEF (IS-TEFM-IS). We further discuss this new NHPP SRGM with two imperfect-debugging assumptions to propose two new NHPP SRGMs, i.e. IS-TEFM-IS-ID1 and IS-TEFM-IS-ID2. Finally these three new NHPP SRGMs and several comparison NHPP SRGMs are applied into two real failure data-sets respectively for investigating the fitting power of the IS-TEFM-IS, IS-TEFM-IS-ID1 and IS-TEFM-IS-ID2. The experimental results show that the inflected S-shaped NHPP SRGMs considering IS-TEF and imperfect indeed can yield the best accurate estimation results than the other comparison SRGMs. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1630